TECHNICAL AND MANAGERIAL DETERMINANTS OF THREE-PHASE INDUCTION MOTOR EFFICIENCY: A CROSS-INDUSTRY COMPARATIVE LITERATURE STUDY - Surya Adi Saputra; Deny Hadi Siswanto (CV. Denasya Smart Publisher, 2025)
This study aims to examine the efficiency of three-phase induction motors and the factors influencing it through a literature study approach with a descriptive-analytical design. Secondary data were obtained from reputable journals, books, technical standards (IEC 60034-30-1, IEC 60085, PUIL 2011), government regulations, and industrial research reports. The analysis was conducted comparatively against findings from the palm oil, paper, and manufacturing sectors to identify similarities, differences, and key factors for improving efficiency. The results indicate that motor efficiency is affected by workload, operating temperature, voltage stability, motor age, the implementation of Occupational Health and Safety (OHS), and compliance with technical standards. Operating at near-optimal loads, performing routine maintenance, using Variable Speed Drives (VSD), and IoT-based monitoring have been proven to enhance efficiency and extend motor lifespan. The application of OHS measures and adherence to international/national standards maintain system reliability and reduce energy losses. This study recommends integrating technical and managerial strategies, including selecting high-efficiency class motors, optimizing load settings, implementing real-time monitoring, and providing technical training, to achieve efficient, safe, and sustainable motor performance while supporting industrial competitiveness amidst the demands for energy efficiency and environmental sustainability